2007
DOI: 10.3389/neuro.03.004.2007
|View full text |Cite
|
Sign up to set email alerts
|

Fast-reset of pacemaking and theta-frequency resonance patterns in cerebellar golgi cells: Simulations of their impact in vivo

Abstract: The Golgi cells are inhibitory interneurons of the cerebellar granular layer, which respond to afferent stimulation in vivo with a burst-pause sequence interrupting their irregular background low-frequency firing (Vos et al., 1999a. Eur. J. Neurosci. 11, 2621-2634. However, Golgi cells in vitro are regular pacemakers (Forti et al., 2006. J. Physiol. 574, 711-729), raising the question how their ionic mechanisms could impact on responses during physiological activity. Using patch-clamp recordings in cerebellar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
167
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(180 citation statements)
references
References 46 publications
8
167
1
Order By: Relevance
“…Although the silent period has long been observed in other GoC preparations (Eccles et al 1966), its function and origin have remained unclear. Proposed mechanisms are intrinsic membrane currents of the GoC (Solinas et al 2007), activation of metabotropic glutamate receptors of type 2 (Watanabe et al 1998), or the dynamics of the network (Dugué et al 2009;Maex and De Schutter 1998). The clear current source we found in the granular layer near the GoC recording position and coincident with the silent period (Figs.…”
Section: The Sequence Of Synaptic Activations Probed With a 1d Electrmentioning
confidence: 83%
See 1 more Smart Citation
“…Although the silent period has long been observed in other GoC preparations (Eccles et al 1966), its function and origin have remained unclear. Proposed mechanisms are intrinsic membrane currents of the GoC (Solinas et al 2007), activation of metabotropic glutamate receptors of type 2 (Watanabe et al 1998), or the dynamics of the network (Dugué et al 2009;Maex and De Schutter 1998). The clear current source we found in the granular layer near the GoC recording position and coincident with the silent period (Figs.…”
Section: The Sequence Of Synaptic Activations Probed With a 1d Electrmentioning
confidence: 83%
“…However, a modeling study could not exclude the slowly propagating parallel fibers as a secondary source of excitation (Volny-Luraghi et al 2002), and alternative pathways exist (see DISCUSSION). In addition, both the initial burst-like response and the long-lasting suppression could reflect the activation of afferent synapses or, alternatively, be generated by intrinsic membrane mechanisms (Solinas et al 2007). Moreover, despite their stereotypical response patterns to peripheral stimulation, GoCs have larger receptive fields and a lower response selectivity than mossy fibers (Prsa et al 2009).…”
mentioning
confidence: 99%
“…In many cases modeling has led to surprising results contradicting, in part, the experimental expectations. For example, modeling showed that a spatial separation of calcium channel types was not needed to generate both calcium plateaus and calcium spikes in Purkinje cells (De Schutter and Bower 1994) and that in cerebellar Golgi cells the I h current does not actively participate to subthreshold oscillations that drive spontaneous firing (Solinas et al 2007). At a more general level, combined modeling and experimental work has shown that homeostatic control of channels make specific links between channels and firing behaviors tenuous and that, in many cases trying to explain data with a unique model may be a fallacy (Achard and De Schutter 2006;Marder and Goaillard 2006).…”
mentioning
confidence: 99%
“…The persistent Na + current (I NaP ) is a threshold current which have been found in neocortical and hippocampal pyramidal neurons (French and Gage, 1985;Stafstrom et al, 1985), hippocampal and cerebellar interneurons (Solinas et al, 2007;Boehlen et al, 2011), and many other neurons in different brain regions (Crill, 1996). I NaP was activated positive to -65 mV and could be blocked by tetrodoxin (TTX, 1 µM).…”
Section: Introductionmentioning
confidence: 99%
“…Persistent Na + currents have been shown to contribute importantly to intrinsic oscillations of some central neurons (Klink and Alonso, 1993;Gutfreund et al, 1995;Hutcheon et al, 1996;Pape and Driesang, 1998;Hu et al, 2002), in cerebellar interneurons (Solinas et al, 2007) and hippocampal stratum radiatum interneurons (Boehlen et al, 2011). In rat neocortex, regular spiking (RS) and intrinsic bursting (IB) neurons exhibited resonance at resting membrane potentials.…”
Section: Introductionmentioning
confidence: 99%